Numerical Simulation of a Periodic Quasi-Switching Mode of Flow around a Conical Dimple with a Slope Angle of 10 Degrees on the Wall of a Narrow Channel Using URANS - Sergey Isaev (MDPI AG, 2021)
The applicability of the solution of the unsteady Reynolds-averaged Navier–Stokes equations (URANS) for the numerical simulation of the periodic quasi-switching regime of vortex generation and heat transfer in a deep conical dimple with a slope angle of <semantics>10∘</semantics> on the wall of a narrow channel is substantiated. To calculate the turbulent regime, the model of shear stress transfer by Menter 2003, modified taking into account the influence of the curvature of streamlines within the framework of the Rodi-Leshziner-Isaev approach, is used. At Reynolds number <semantics>Re=104</semantics>, the oscillation period of the transverse <semantics>Rz</semantics> and longitudinal forces <semantics>Rx</semantics>, as well as the total heat transfer <semantics>Numm</semantics> to the control section of the heated channel wall with a dimple, is set equal to 60, which corresponds to the Strouhal number <semantics>St=0.0167</semantics>. Computer visualization of swirling jet-vortex flows demonstrates focus-type sources on the side faces of the dimple. In the self-oscillating mode, a two-cell vortex system is formed with different intensities at the oscillation period <semantics>Rz</semantics>. Periodic changes in friction, Nusselt numbers and temperature are recorded in the longitudinal and transverse median sections of the dimple and reflect the oscillations of the vortex structure from left to right and from right to left. The formation of a fan jet is shown, which oscillates relative to the plane of longitudinal symmetry, causing a redistribution of power and thermal loads.